Assessment of Post-Stroke Insomnia and Quality of Life among Stroke Survivors of Dhaka City: A Cross-sectional Study - Fatema Khanam; Sajia Afrin; Afroza Irin (Interdisciplinary Journal of Epidemiology and Public Health, 2025)
Background: Stroke is frequently a disastrous event that often leads to short or long-term neurological impairment and functional disability, affecting survivors’ quality of life (QoL).  Objective: To assess the prevalence of post-stroke insomnia and the status of QoL among stroke survivors. Methods: Descriptive cross-sectional study using mixed methods among 85 stroke survivors at the Centre for the Rehabilitation of the Paralysed (CRP) in Dhaka, Bangladesh.  Convenience sampling was employed for sample selection, and data were collected using a self-reported, semi-structured Bengali questionnaire from October 2019 to January 2020. Analysis was performed using SPSS and MS Excel.  Results: Among respondents, 20% reported experiencing severe clinical insomnia, 24.7 % had clinical insomnia, and 15.3% had sub-threshold insomnia. Regarding QoL, 36.5% needed ‘Some Help’, 32.9% needed ‘A little Help,’ and 15.3% needed ‘A lot of Help’ from others. Insomnia was more prevalent among survivors aged 70 and above (OR 11.28), those who faced hemorrhagic stroke (OR 0.15), and individuals with diabetes (OR 3.08). QoL was significantly affected by age 57-69 years (OR 0.79), full-time worker (OR .22), hemorrhagic stroke (OR 0.29), and diabetes (OR 4.40). Conclusion: The result indicates that insomnia and reduced quality of life among stroke survivors were highly prevalent, especially among older adults, diabetics, and patients affected by hemorrhagic stroke. These correlations underscore the need for multidisciplinary therapies and targeted screening to effectively treat sleep disorders and enhance day-to-day functioning. Improving post-stroke care with customized rehabilitation techniques may significantly enhance the long-term outcomes and overall well-being of this vulnerable population.